Identification and characterization of sugar-regulated promoters in Chaetomium thermophilum - Reislöhner, Sven; Schermann, Geza; Kilian, Max; Santamaría-Muñoz, Daniela; Zimmerli, Christian; Kellner, Nikola; Baßler, Jochen; Brunner, Michael; Hurt, Ed (BMC biotechnology, 2023)
The thermophilic fungus Chaetomium thermophilum has been used extensively for biochemical and high-resolution structural studies of protein complexes. However, subsequent functional analyses of these assemblies have been hindered owing to the lack of genetic tools compatible with this thermophile, which are typically suited to other mesophilic eukaryotic model organisms, in particular the yeast Saccharomyces cerevisiae. Hence, we aimed to find genes from C. thermophilum that are expressed under the control of different sugars and examine their associated 5’ untranslated regions as promoters responsible for sugar-regulated gene expression. To identify sugar-regulated promoters in C. thermophilum, we performed comparative xylose- versus glucose-dependent gene expression studies, which uncovered a number of enzymes with induced expression in the presence of xylose but repressed expression in glucose-supplemented media. Subsequently, we cloned the promoters of the two most stringently regulated genes, the xylosidase-like gene (XYL) and xylitol dehydrogenase (XDH), obtained from this genome-wide analysis in front of a thermostable yellow fluorescent protein (YFP) reporter. With this, we demonstrated xylose-dependent YFP expression by both Western blotting and live-cell imaging fluorescence microscopy. Prompted by these results, we expressed the C. thermophilum orthologue of a well-characterized dominant-negative ribosome assembly factor mutant, under the control of the XDH promoter, which allowed us to induce a nuclear export defect on the pre-60S subunit when C. thermophilum cells were grown in xylose- but not glucose-containing medium. Altogether, our study identified xylose-regulatable promoters in C. thermophilum, which might facilitate functional studies of genes of interest in this thermophilic eukaryotic model organism.